Иммуногистохимическая характеристика лимфоцитарной реакции очага вторично хронического воспаления - Татарко, С.В. (Таврический медико-биологический вестник, 2010)
За даними імуногістохімічного дослідження, при вторинно хронічному запаленні у вогнищі спостерігається виражена лімфоцитарна реакція з переважанням клітинної імунної ланки над гуморальною. Останнє проявляється вираженим перевищенням кількості T-лімфоцитів над В- лімфоцитами. Відбувається інтенсивний синтез IgE і, порівняно з цим, більш низький – IgM і IgG. В той же час серед популяції T-лімфоцитів в ранні строки запалення (до 5-ї доби) переважають T-хелпери над T-супресорами, а в більш пізні – навпаки. According to immunohistochemical studies, at secondary chronic inflammation pronounced lymphocytic reaction with considerable prevalence of cellular over humoral component is observed. This is manifested by pronounced increase of the number of T-cells comparing to B-cells. Intensive synthesis of IgE and, comparing to this, lower synthesis of IgM and IgG are observed. At the same time at early terms of inflammation (up to 5 days) T-helpers predominate over T-suppressors, while in later terms it is vice versa.